Research of the Fast Modeling for Spiral Bevel Gear with Spherical Involute based on the SWEEP - Li Tongzhong; Fan Jun; Adayi·Xieeryazidan (Jixie chuandong)
The parametric modeling of spiral bevel gear is of great significance to its further research on tooth contact analysis in its digitized design.From the precision of spiral bevel gear tooth with spherical involute tooth profile,the principle of forming the spherical involute is used to solve the parametric equations of all parts of tooth profile curve.Combining the unique advantages of Frenet frame in the SWEEP surface modeling,a modeling method of tooth surface of spiral bevel gear with the spherical involute is presented based on the SWEEP.Finally,the model is created by using the transverse tooth profiles through the SWEEP method.The numerical example verified that this method can finish fast and accurate parametric modeling process of the spiral bevel gear tooth surface,a new access to design of the spiral bevel gear is provided.